General Nexus Between Water and Electricity Use and Its Implication for Urban Agricultural Sustainability: A Case Study of Shenzhen, South China - Wen-jiang LI; Lin-jun LI; Guo-yu QIU (Journal of Integrative Agriculture, 2013)
Although water and energy resources are well-recognized concerns regarding economic and social development sustainability, little specific research has focused on both water and energy problems at the same time. This study analyzed the water and electricity-use patterns in Shenzhen, South China during 2001-2009. A curve regression method was used to examine the relationship between water and electricity use per gross domestic product (GDP) in Shenzhen and its three sectors, i.e., agriculture, industry & construction, and residential life & services. Results showed that agriculture only covered less than 10% of water and electricity use in Shenzhen, while industry & construction and residential life & services accounted for more than 90% of water and electricity use in Shenzhen, which coincided with the city's industrial structure. The water and electricity use per GDP in agriculture was the biggest among three sectors in Shenzhen during 2001-2009, which means inefficiency of water and electricity use in agriculture. Due to transitioning to advanced materials and manufacturing, both water and electricity use per GDP in industry & construction decreased during 2001-2009 and their utilization efficiencies gradually increased over time. The same held true for those in residential life & services transformed toward modern business, creative culture, finance services, etc. Derived from the survival of the fittest in competing for limited water and electricity resources, agriculture in Shenzhen has been gradually substituted by industry & construction and residential life & services, with much higher efficiencies of water and electricity use. And traditional agriculture will not be sustainable in the process of urbanization and industrialization, except high-tech intensive agriculture with low water and energy cost. Furthermore, by means of curve regression, we found that there was a significant quadratic relationship between water use per GDP and electricity use per GDP in the entire city and its three sectors. Suitable industrial transformation and advancement was a very effective way to save water and energy for modern cities. This can provide some reference for systematic planning and design of water and electricity allocation and use in agriculture, industry & construction and residential life & services in a city.